Pengaruh Pelatihan dan Motivasi Kerja terhadap Produktivitas Pekerja di PT. Hayyu Pratama Kaltim - Rizka Ariani; Jubaidi Jubaidi; Rinda Sandayani Karhab (Dharma Ekonomi, 2025)
This study aims to assess the effect of training and work motivation on worker productivity at PT Hayyu Pratama Kaltim. The research method uses quantitative. The population in this study were 92 permanent employees and a sample of 48 employees selected using the Slovin formula. Data obtained through the results of questionnaires distributed using google forms. The data analysis method used is multiple linear regression with testing using the t test and F test which is first carried out the Classical Assumption test. The results obtained show that training has a positive and significant effect on worker productivity, work motivation has a positive and insignificant effect on worker productivity, while training and work motivation have a positive and significant effect on worker productivity.